2021
DOI: 10.1016/j.psj.2021.101211
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the energy and digestible lysine contents of the diet on performance and egg quality traits of brown-egg laying hens from 19 to 59 weeks of age

Abstract: The influence of nutrient density and standardized ileal digestible lys ( DLys ) content of the diet on egg production and egg quality traits, was studied in brown-egg laying hens from 19 to 59 wk of age. The experimental design was completely randomized with eight treatments arranged as a 2×4 factorial with two AMEn concentrations (2,680 and 2,780 kcal/kg) and four levels of DLys (0.68, 0.72, 0.76, and 0.80%). Each treatment was replicated nine times and the experimental unit was a cage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…In the current study diet nutrient density did not influence hen-day EP at 24, 69 ( Muir et al, 2022b ) or 89 WOA ( Table 4 ), nor cumulative EP from 18 to 24, 18 to 50 ( Muir et al, 2022a ), 18 to 69 ( Muir et al, 2022b ) or 18 to 89 WOA ( Table 5 ). Scappaticcio et al (2021) also report similar EP from 19 to 59 WOA from hens receiving diets of different energy levels. In contrast diets of higher energy levels have been reported to continuously improve hen-day EP ( Latshaw et al, 1990 ) while others found EP varied across the production period.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In the current study diet nutrient density did not influence hen-day EP at 24, 69 ( Muir et al, 2022b ) or 89 WOA ( Table 4 ), nor cumulative EP from 18 to 24, 18 to 50 ( Muir et al, 2022a ), 18 to 69 ( Muir et al, 2022b ) or 18 to 89 WOA ( Table 5 ). Scappaticcio et al (2021) also report similar EP from 19 to 59 WOA from hens receiving diets of different energy levels. In contrast diets of higher energy levels have been reported to continuously improve hen-day EP ( Latshaw et al, 1990 ) while others found EP varied across the production period.…”
Section: Discussionsupporting
confidence: 55%
“…Aligning with our findings of improved FCR during the earlier stages of the production cycle, Wu et al (2005) also reported an improvement in FCR between 21 and 36 WOA for hens receiving a HND diet. More nutrient dense diets also improved hen feed efficiency across longer 19 to 59 WOA ( Scappaticcio et al, 2021 ) and 19 to 70 WOA ( dePersio et al, 2015 ) production phases. However, it should also be noted that the studies of Wu et al (2005) , Scappaticcio et al (2021) , and dePersio et al (2015) involved the HND diet being fed throughout the entire study period, compared to its short-term provision from 18 to 24 WOA only in the current study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In another study, (34), suggested that supplementing diets that enhance upregulation of AA transporters would enhance albumen synthesis and quality. On the other hand, dietary threonine (186), total sulfur amino acid (178), D-lysine (187), amino acid-complexed manganese (168) and L-citrulline, a non-protein AA (188) did not affect albumen quality. However, decreasing albumen indices with dietary AA supplementation may be due to decreased albumen synthesis (33) and the feeding regime of the AA (179).…”
Section: Amino Acid and Dietary Protein Level Or Sourcesmentioning
confidence: 86%
“…Furthermore, egg production is sensitive to amino acid nutrition imbalance [34]. There is evidence that essential amino acids (methionine, threonine, isoleucine, and lysine) exerted a positive influence on egg production [35][36][37], probably because amino acids provide support for high protein synthesis which is often a prerequisite for improved egg production. Thus, the improved digestibility of these essential amino acids in this study suggests their utilization for egg production.…”
Section: Effects Of Fructooligosaccharides On Laying Performancementioning
confidence: 99%